PENGEMBANGAN KOMODITI PERTANIAN TANAMAN PANGAN DAN HORTIKULTURA SAYURAN KAWASAN ANDALAN KOTA PARE-PARE PROVINSI SULAWESI SELATAN - -, Rusida (Jurnal Ilmiah Ecosystem, 2020)
The purpose of this study was to determine the types of superior commodities of agricultural food crops and vegetable horticulture which are the production bases in the mainstay area of Parepare City, South Sulawesi Province. The results of the LQ analysis show, (i) Bacukiki District is very superior for agricultural crops of paddy rice commodity, Ujung and Soreang District for corn commodity, West Bacukiki District for peanut commodity and mung bean commodity and West Bacukiki District and Ujung for cassava commodity, (ii) West Bacukiki and Ujung Subdistricts are superior for horticulture vegetables of kangkung commodity, Bacukiki Subdistricts are superior for chilli, eggplant and tomato commodities, Bacukiki and Soreang Districts are very superior for spinach commodities, Soreang District is very superior for the commodities of cabbage and mustard and Subdistricts Bacukiki and West Bacukiki are very superior for long bean commodities (iii) The analysis of locality results for agricultural commodities of food crops shows that there are no districts that have a locality coefficient greater than or equal to one, for horticulture Shuran there are districts with greater locality coefficients or equal one, (iv) Results a analysis of specialization coefficients for agricultural food crop commodities shows that there are no districts that have a specialization coefficient greater than or equal to one and for vegetable horticultural commodities there is no district that has a specialization coefficient greater than or equal to one